Green synthesis of Silver nanoparticles using the plant extract of Shikakai and Reetha. (2018) - Kumar Sur, Ujjal; Ankamwar, Balaprasad; Karmakar, Sanat; Halder, Animesh; Das, Pulak
Abstract: The recent development in the eco-friendly and cost-effective green synthesis of metal and semiconductor nanoparticles using various natural resources such as microorganisms, plant, flower and fruit extracts is an emerging area of nanotechnology. In this paper, we have described the green synthesis of silver nanoparticles using the plant extract of Shikakai and Reetha. The biosurfactant molecules present inside the plant extract play a significant role both as stabilizing and reducing agents. We have characterized the biosynthesized silver nanoparticles by UV-visible spectroscopy, X-ray diffraction (XRD) study and Transmission electron microscopy (TEM). The biosynthesized Ag nanoparticles were further utilized as an effective SERS active substrate for the detection of dye molecule and bacteria.